CLINICO-PATHOLOGICAL PRESENTATION AND THERAPEUTIC OPTIONS FOR HAIRY CELL LEUKEMIA - Jameel, Abid; Chiragh, Sadaf; Iqbal, Saira; Farooq, Muntajeeb (Journal of Postgraduate Medical Institute, 2012)
Objective: To look at clinical and hematological presentation as well as treatment outcome of patients with diagnosis of Hairy Cell Leukemia (HCL) in our population. Methodology: All patients diagnosed with HCL by morphological and immunohistochemical methods presenting to Medical Oncology Ward at Hayatabad Medical Complex, Peshawar since August 2008 were included in the study. Results: Out of 7 patients diagnosed with HCL, 6 were male and 1 was female (M:F ratio 6:1). Median age at diagnosis was 44 years. Fever, pallor, palpitations and fatigue were the commonest presenting complaints. Spleenomegaly was noted in all patients (100%). Pancytopenia was noted in all patients at presentation. Five patients were treated with Interferon while 2 were treated with Cladribine. At 18 months of follow-up, one out five patients treated with IFN had relapse while both the patients treated with Cladribine were in complete remission. Conclusion: Our study showed that HCL patients present at a younger age in our region but further studies with larger sample size are required to confirm this. All patients showed a complete response to Interferon and Cladribine with all patients alive at 18 months of follow-up.